Autonomous DuffingHolmes Type Chaotic Oscillator - Tamaševičius, A.; Bumelienė, S.; Kirvaitis, R.; Mykolaitis, G.; Tamaševičiūtė, E.; Lindberg, E. (Elektronika ir Elektrotechnika, 2009)
A novel DuffingHolmes type autonomous chaotic oscillator is described. In comparison with the well-known nonautonomous DuffingHolmes circuit it lacks the external periodic drive, but includes two extra linear feedback subcircuits, namely a direct positive feedback loop, and an inertial negative feedback loop. In contrast to many other autonomous chaotic oscillators, including linear unstable resonators and nonlinear damping loops, the novel circuit is based on nonlinear resonator and linear damping loop in the negative feedback. SPICE simulation and hardware experimental investigations are presented. Fairly good agreement between numerical and experimental results is observed. Ill. 7, bibl. 25 (in English; summaries in English, Russian and Lithuanian).